Biodegradable and Peroxidase‐Mimetic Boron Oxynitride Nanozyme for Breast Cancer Therapy. Issue 16 (30th June 2021) - Zeng, Lula; Han, Yuxin; Chen, Zhiwei; Jiang, Kang; Golberg, Dmitri; Weng, Qunhong
Abstract: Nanomaterials having enzyme‐like activities are recognized as potentially important self‐therapeutic nanomedicines. Herein, a peroxidase‐like artificial enzyme is developed based on novel biodegradable boron oxynitride (BON) nanostructures for highly efficient and multi‐mode breast cancer therapies. The BON nanozyme catalytically generates cytotoxic hydroxyl radicals, which induce apoptosis of 4T1 cancer cells and significantly reduce the cell viability by 82% in 48 h. In vivo experiment reveals a high potency of the BON nanozyme for breast tumor growth inhibitions by 97% after 14‐day treatment compared with the control, which are 10 times or 1.3 times more effective than the inert or B‐releasing boron nitride (BN) nanospheres, respectively. This work highlights the BON nanozyme and its functional integrations within the BN nanomedicine platform for high‐potency breast cancer therapies. Abstract : An artificial peroxidase‐like nanozyme is designed based on a biodegradable boron oxynitride nanostructure, which generates hydroxyl radical efficiently and durably, reduces breast cancer cell viability by 82% in 48 h, and inhibits the cancer growth by 97% in 14 days.